Sensitivitas Black Garlic Terhadap Pertumbuhan Salmonella Sp. - Widhowati, Dyah; Mudji, Era Hari; Prakoso, Yos Adi; Aulia, Qoryza (VITEK : Bidang Kedokteran Hewan, 2022)
The aimed of this study to determine the sensitivity of Black garlic to the growth of Salmonella sp. with the disc paper test method (Kirby-bauer) as many as five treatments and five repetitions, P0- as a negative control using DMSO, P0+ as a positive control with chloramphenicol 30 μg. P1 as a treatment with a concentration of Black garlic of 80%, P2 as a treatment with a concentration of Black garlic of 90%, and P3 as a treatment with a concentration of Black garlic of 100%. Salmonella sp. inhibition zone results namely 00.0 mm at negative control, 10.28 mm at 80% concentration, 12.33 mm at 90% concentration, 14.56 mm at 100% concentration, and 29.00 mm at positive control. PIDG results were 0.00% in negative control, 71.40% at 80% concentration, 105.54% at 90% concentration, 142.68% at 100% concentration, and 383.42% in positive control. The data were obtained using One Way ANOVA which showed antibacterial sensitivity in Black garlic to Salmonella sp. with signification (P<0.05) so that it had a noticeable difference. The results of the disc paper test (Kirby-bauer) stated that Black garlic with a concentration of 100% has an active compound that is betterfor its activities in inhibiting the growth of Salmonella sp.